REGULATORY TSCELLS WITH SUPPRESSIVE ACTIVITY IN SURGICAL SEPSIS - E. V. Kurganova; M. A. Tikhonova; E. I. Streltzova; A. A. Ostanin; E. R. Chernykh; V. A. Kozlov (Медицинская иммунология, 2014)
Abstract. Present work aims to investigate functioning of the regulatory T-cells with suppressor activity in surgical sepsis. It has been shown that the septic patients with decreased T cell proliferation are characterized by enhanced relative contents of СD4+СD25+ lymphocytes, including СD4-CD25high. Moreover, a reverse correlation has been revealed between СD4+CD25+high and anti-CD3-induced proliferative response of mononuclear cells (MNC).Increased ratio of СD4+СD25+ cells is associated with arising suppressive activity of MNC, which is partially abrogated by addition of rIL-2. It should be noted that the depletion of CD25+ subpopulation is accompanied by increased T cell proliferation. Hence, a decrease in T cell proliferative activity in surgical sepsis is coupled with naturally occurring СD4+СD25+ regulatory T-cells (Trn).Furthermore, it has been demonstrated that the suppressive activity of MNCs in septic patients is mediated by soluble factors, in particular, IL-10. Indeed, septic patients are characterized by increased level of IL-10 production and enhanced number of CD4+IL-10+ T-cells. Addition of neutralizing anti-IL-10 antibody partially abrogated the suppressive activity of MNC supernatants. Thus, our study demonstrated that inducible regulatory T cells (Tr1) coupled to the naturally occurring СD4+СD25+ regulatory T-cells (Trn) actively contribute to genesis of immune pathology in sepsis.